Changes in oral health-related quality of life before and after dental treatment in 8–12-year-old Costa Rican schoolchildren - Jiménez-Lobo, Juliana; Batista-Cárdenas, Daniela; Aguilar-Cubillo, Ariadna; Gómez-Fernández, Adrián; Ramírez, Karol (Frontiers in Dental Medicine, 2023)
Aims: The aims of this study were to 1) evaluate oral health-related quality of life (OHRQoL) in 8 to 12-year-old Costa Rican schoolchildren before and after dental treatment and 2) collect clinical and sociodemographic characteristics. Methods: Participants completed the Child Oral Health Impact Profile-Short Form (COHIP-SF-19) questionnaire before and after dental treatment. One of the parents was asked to fill a sociodemographic survey. Patients were treated for caries, hypomineralisations and malocclusions. Prevalence of this conditions were assessed from the patient’s electronic dental record. Results: Eighty participants (39 male and 41 female, average age: 9.4 ±1.0 years) were recruited. The prevalence of dental caries was 56.1% with a mean deft and DMFT score of 3,15 ±0.96 and 2.22 ±0.77, respectively. Prevalence of hypomineralisations was 53.7% and malocclusions 82.9%. The Simplified Oral Hygiene Index before treatment was 1.45±0.45 and afterwards, 1.42±0.43. Mean COHIP-SF-19 total score decreased from 53,7 ±7,8 before dental treatment to 31,4 ±4,2 after treatment. Improvements in all subdomains were also observed. Regarding sociodemographic characteristics, 65% of the patients lived in San José, Costa Rica’s capital city, and 56.3% of the studied population belonged to a low-income family. The majority of parents reported incomplete high school. Regarding the number of family members living in the same house as the patient, an average of 4 people was reported. In relation to family structure, 58.8% of the child’s parents lived together, either married or free union. As for household owning, 53.8% of parents reported owning their house, 36.3% lived in a rented house and 10% lived in a borrowed home. Conclusion: This is the first study evaluating OHRQoL in Costa Rican schoolchildren. Dental interventions in our clinical setting improved self-perceptions of oral health and quality of life.